Fuel efficiency effect on car buying choice (2016)
The results of a research to study the fuel efficiency effect in acquiring a new vehicle are presented. The methodology is based on applying a stated preference survey in the context of a choice experiment with two unlabeled alternatives, which are characterized by the car cost and fuel efficiency.Based on the data collected, a Multinomial Logit model was estimated, which allowed to study different choice scenarios. On average, it was found that individuals are willing to pay up to 1.020.000 Colombian pesos by a new vehicle which improves fuel efficiency at 1 kilometer/gallon. This value may be useful as reference for the automotive industry in the effort to produce higher performance vehicles.